ETIKA BERSOSIALISASI DENGAN AL-QUR’AN - Mujiburrahman Mujiburrahman; Ibnu Ali; Ali Tohir (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2023)
Socializing with the Qur'an is a valuable experience for a Muslim. The experience of socializing with the Qur'an can be revealed through speech, writing, or actions. Moreover, the Al-Qur'an is a guide for the life of Muslims that was born from the word of Allah SWT. As a holy book that contains His word, of course, Muslims respect and highly respect the Qur'an. From this description, the author will describe several ethics in socializing with the Qur'an, both those described in the Qur'an, Hadith and the opinions of the scholars. This type of research is library research (library research), the author seeks to collect data concerning the ethics of socializing with the Qur'an which concerns the importance of respecting or glorifying the Qur'an. From the results of research that has been carried out on the ethical theme of socializing with the Qur'an, including: Having a sincere intention to worship Allah SWT, Cleaning the mouth, Reading the Qur'an in Purified Condition, Clean place, Facing Qibla, Starting Qiraah with Reciting Ta'awudz, Beginning the Surah with Basmalah, Mentadabburi Verses, Reading the Qur'an with tartil, Not allowed to read the Al-Qur'an in a language other than Arabic, Read the Al-Qur'an in the order of the Mushaf, Read the Al-Qur'an 'an by looking at the Mushaf, it is sunnah to pray when completing the Qur'an with good prayers, placing the Qur'an in a proper and high place, and many other ethics that have not been mentioned in this article.